THE EXPERINCE OF CONSECUTIVE INTERPRETING AND INTERPRETERS' NOTE-TAKING TECHNIQUE TEACHING - Оксана Куца (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
Necessity of highly experienced consecutive interpreters training is grounded taking into account the modern needs of interpretation market. Advantages of consecutive interpreting in modern communicational space are revealed. Advantages and disadvantages of consecutive interpreting in comparison with simultaneous one are found out. Theoretical framework of the course is featured. Video materials selection requirements for practical work for consecutive interpreting skills and habits development in close to the real conditions are presented. Subsystems of exercises for developing consecutive interpreting skills and habits (preparatory; for developing habits and for developing skills) are indicated, characterized and instanced.